Proteomic View of Interactions of Shiga Toxin-Producing Escherichia coli with the Intestinal Environment in Gnotobiotic Piglets. - Rembert Pieper; Quanshun Zhang; David J Clark; Prashanth P Parmar; Hamid Alami; Moo-Jin Suh; Srilatha Kuntumalla; John C Braisted; Shih-Ting Huang; Saul Tzipori (PLoS ONE, 2013)
Shiga toxin (Stx)-producing Escherichia coli cause severe intestinal infections involving colonization of epithelial Peyer's patches and formation of attachment/effacement (A/E) lesions. These lesions trigger leukocyte infiltration followed by inflammation and intestinal hemorrhage. Systems biology, which explores the crosstalk of Stx-producing Escherichia coli with the in vivo host environment, may elucidate novel molecular pathogenesis aspects.Enterohemorrhagic E. coli strain 86-24 produces Shiga toxin-2 and belongs to the serotype O157:H7. Bacterial cells were scrapped from stationary phase cultures (the in vitro condition) and used to infect gnotobiotic piglets via intestinal lavage. Bacterial cells isolated from the piglets' guts constituted the in vivo condition. Cell lysates were subjected to quantitative 2D gel and shotgun proteomic analyses, revealing metabolic shifts towards anaerobic energy generation, changes in carbon utilization, phosphate and ammonia starvation, and high activity of a glutamate decarboxylase acid resistance system in vivo. Increased abundance of pyridine nucleotide transhydrogenase (PntA and PntB) suggested in vivo shortage of intracellular NADPH. Abundance changes of proteins implicated in lipopolysaccharide biosynthesis (LpxC, ArnA, the predicted acyltransferase L7029) and outer membrane (OM) assembly (LptD, MlaA, MlaC) suggested bacterial cell surface modulation in response to activated host defenses. Indeed, there was evidence for interactions of innate immunity-associated proteins secreted into the intestines (GP340, REG3-γ, resistin, lithostathine, and trefoil factor 3) with the bacterial cell envelope.Proteomic analysis afforded insights into system-wide adaptations of strain 86-24 to a hostile intestinal milieu, including responses to limited nutrients and cofactor supplies, intracellular acidification, and reactive nitrogen and oxygen species-mediated stress. Protein and lipopolysaccharide compositions of the OM were altered. Enhanced expression of type III secretion system effectors correlated with a metabolic shift back to a more aerobic milieu in vivo. Apparent pathogen pattern recognition molecules from piglet intestinal secretions adhered strongly to the bacterial cell surface.